Sequential dilation strategy in stent therapy of the aortic coarctation: A single centre experience. (15th May 2021) - Bambul Heck, Pinar; Fayed, Mohamed; Hager, Alfred; Cesna, Sigitas; Georgiev, Stanimir; Tanase, Daniel; Hörer, Jürgen; Ewert, Peter; Eicken, Andreas
Abstract: Background: In our study, we sought to analyse the mid-term results after interventional aortic coarctation (CoA) stenting with sequential dilation of the stent. Methods: The data of all 218 patients, who are above the age of 6 years and underwent CoA-stent implantation in our hospital, were retrospectively analysed on the rate of re-interventions, complications and arterial hypertension at a follow-up time of 31 months. To avoid any aortic complications, stents were deployed primarily not in full size and a second cardiac catheterisation for further dilatation was scheduled within 6–12 months after the stent implantation. Results: The median peak invasive systolic pressure gradient declined significantly from 26.2 mmHg to 2.7 mmHg after stenting. There was one procedure related death due to an aortic rupture after stent implantation. There were in total 33 (15.1%) procedure-related complications including femoral artery complications, stent fracture and stent dislocation (in 9, 9 and 7 patients, respectively). In 85 patients a re-dilatation and in 25 patients a second stent-implantation was necessary at the first re-intervention. The systolic blood pressure declined significantly from 144 mmHg to 131 mmHg after stenting. The number of patients being normotensive changed from 18% before stenting to 78.5% after stenting with adjusted antihypertensive medication. Conclusion: Aortic stenting is an effective means for CoA treatment. With sequential dilation of the stent, a very low rate of life-threatening procedural complications and mortality can be achieved. CoA stenting with proper antihypertensive medications results in better control of blood pressure. Highlights: Endovascular stent implantation is effective means for aortic coarctation treatment. With the sequential dilation of the CoA-stent, a low rate of mortality can be achieved. It also has a very low rate of life-threatening aortic complications. It should be considered for patients with high risk for aortic complications.